Conventional Power System Stabilizer Design - Santra, Swapan; Paul, Subrata (International Journal of Computer Sciences and Engineering, 2025)
Power System Stabilizer (PSS) is used to add damping to generator’s oscillations. It is achieved by modulating the generator’s excitation so as to produce adequate of electrical torque in phase with the rotor speed deviations. In this paper a power system stabilizer has been designed based upon lead-lag compensator and a washout time constant. The effectiveness of the power system stabilizer designed through this method is demonstrated by simulation of a sample power system for various loading conditions using MATLAB.